SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN BUAH PISANG YANG PALING DIMINATI - Irianto Irianto; Sudarmin Sudarmin (STMIK Royal, 2020)
Abstract: as an agrarian country Indonesia has a variety of plants that can produce many different kinds of fruit from farmers, especially on average in each region has farmers who have crops that are suitable and in accordance with the conditions of their respective regions. Banana is one of the most consumed fruits by the people. The banana plant farmers basically have a way to determine their own characteristics or character to determine the good or good fruit and suitable for consumption. Many farmers or fruit enthusiasts often find it difficult to determine the best fruit on bananas, with an alternative available decision support system with the FMCDM method to choose the best fruit from bananas. Fuzzy Multi Criteria Decision Making (FMCDM) is a decision making method that aims to determine the best alternative decisions from a number of alternatives based on certain criteria that will be taken into consideration. From the results of calculations using the above software, the results obtained are alternative (A3) obtaining the largest total integral value compared to other alternatives. Keywords: Banana; decision support system; fuzzy multi criteria decision making Abstrak: sebagai negara agraris Indonesia mempunyai ragam tanaman yang dapat menghasilkan banyak bermacam buah hasil petani, terlebih rata rata di setiap daerah mempunyai petani yang mempunyai tanaman yang cocok dan sesuai dengan kondisi daerah masing masing. Pisang merupakan salah buah yang paling banyak di konsumsi oleh masyarakat. Adapun petani tanaman buah pisang pada dasarnya mempunyai cara untuk menentukan ciri-ciri tersendiri atau karakter untuk menentukan buah bagus atau baik dan layak untuk dikonsumsi. Banyak kadang petani atau peminat buah susah menentukan buah yang terbaik pada buah pisang, dengan adanya alternatif yang ada sistem pendukung keputusan dengan metode FMCDM untuk memilih buah terbaik dari buah pisang. Fuzzy Multi Criteria Decision Making (FMCDM) adalah suatu metode pengambilan keputusan yang bertujuan untuk menetapkan alternatif keputusan terbaik dari sejumlah alternatif berdasarkan beberapa kriteria tertentu yang akan menjadi bahan pertimbangan. Dari hasil perhitungan menggunakan software di atas, diperoleh hasil yaitu alternatif (A3) memperoleh nilai total integral terbesar dibandingkan denganalternatif-alternatif yang lain. Kata Kunci : Buah Pisang; Fuzzy Multi Criteria Decision Making; sistem penunjang keputusan